ENHANCING SUSTAINABILITY AND COMPETITIVENESS IN INDONESIA’S MINING SECTOR: A SYSTEMATIC LITERATURE REVIEW OF ESG IMPLEMENTATION - Suryaputra, Muhammad Irsa; Sayuti, Alfian; Kharunnisa, Kharunnisa; Kanigara, Indra Wahyu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The mining sector plays a pivotal role in Indonesia’s economic development, yet it also faces increasing scrutiny regarding its environmental, social, and governance (ESG) performance. Integrating ESG principles into mining practices, particularly within downstream policies, is essential to ensure both sustainability and global competitiveness. This study aims to (i) assess the importance of ESG implementation within Indonesia’s downstream mining policy, (ii) evaluate the current level of ESG adoption in industrial practices, and (iii) formulate strategies to enhance sustainability and competitiveness based on ESG principles. To achieve these objectives, a Systematic Literature Review (SLR) was employed, synthesizing evidence from academic research, policy documents, and industry reports. The review was conducted in three stages: five articles were analyzed to assess the policy importance of ESG, another five to evaluate adoption in industrial practices, and ten to generate strategic recommendations. Artificial intelligence tools were used to support the review process, ensuring transparency, rigor, and efficiency in screening and synthesizing literature. The findings highlight that while ESG has gained recognition in Indonesia’s mining sector, challenges remain in consistent adoption, stakeholder engagement, and disclosure quality. The study proposes context-specific strategies such as strengthening governance frameworks, improving community participation, and integrating ESG into enterprise risk management. These insights contribute to advancing sustainable mining practices and provide strategic directions for policymakers, industry leaders, and stakeholders seeking to align Indonesia’s mining sector with global ESG standards